Mass production of iPSC-derived platelets toward the clinical application - Akihiro Kayama; Koji Eto (Regenerative Therapy, 2024)
The ex vivo production of platelets from induced pluripotent cells (iPSCs) may offer a safer and sustainable alternative for transfusions and drug delivery systems (DDS). However, the mass production of the clinically required number of iPSC-derived platelets (iPSC-PLTs) is challenging. Here, we introduce recent technologies for mass production and the first-in-human clinical trial using ex vivo iPSC-PLTs. To this end, we established immortalized megakaryocyte progenitor cell lines (imMKCLs) as an expandable master cell bank (MCB) through the overexpression of c-MYC, BMI1 and BCL-XL, which modulated megakaryopoiesis and thrombopoiesis. We also optimized a culture cocktail for maturation of the imMKCLs by mixing an aryl hydrocarbon receptor (AhR) antagonist, SR1/GNF-316; a Rho-associated protein kinase (ROCK) inhibitor, Y-27632/Y-39983; and a small-molecule compound replacing recombinant thrombopoietin (TPO), TA-316. Finally, we discovered the importance of turbulence on the manufacturing of intact iPSC-PLTs, allowing us to develop a turbulence-based bioreactor, VerMES. Combination of the MCB and VerMES enabled us to produce more than 100 billion iPSC-PLTs, leading to the first-in-human clinical trial. Despite these advancements, many challenges remain before expanding the clinical implementation of this strategy.